Use of the Dexamethasone-Corticotrophin Releasing Hormone Test to Assess Hypothalamic-Pituitary-Adrenal Axis Function in Rheumatoid Arthritis. (13th September 2009) - Hasan, Eman A.; Jessop, David S.; Power, Lynsey L.; Monk, Paul T.; Kirwan, John R.
Abstract : Objectives . Hypothalamic-Pituitary-Adrenal axis function may be abnormal in rheumatoid arthritis (RA). A pilot study in 7 patients suggested impaired glucocorticoid feedback in some patients after the dexamethasone-corticotrophin releasing hormone (CRH) test. This study aimed to investigate the dexamethasone-corticotrophin releasing factor test in a larger group of patients and relate the results to characteristics of the disease. Methods . Outpatients with active RA (≥ 3 swollen and tender joints and C-reactive protein > 10 mg/L) took dexamethasone (1.5 mg) at 23:00 hour in the evening. Next day, baseline saliva and plasma samples were collected, CRH was infused at 11:00 hour, and 4 serial blood and saliva samples were collected. Plasma samples were stored at− 80 ∘ C and a radioimmunoassay performed for saliva and plasma cortisol. Results . All 20 participants showed normal dexamethasone suppression and mounted no response to the CRH challenge. In samples with measurable cortisol, there was a strong correlation between saliva and plasma values (r = 0.876, n = 26, P < .01 ). Conclusion . No abnormalities were found in the Dexamethasone-CRH test in RA patients in contrast to a previous pilot study. Salivary cortisol measurement may offer an alternative noninvasive technique to plasma cortisol in RA patients in future studies.